It's economic size, stupid! How global advocacy mirrors state power. Issue 4 (10th February 2020) - Hanegraaff, Marcel; Poletti, Arlo
Abstract: Numerous empirical studies suggest that global interest communities are heavily biased in favor of wealthier countries. This research note critically reviews these works suggesting that they (i) lack a benchmark to assess the biased nature of global interest communities and (ii) conflate the concepts of "wealth" (based on GDP per capita) and "economic power" (based on GDP) into one analytical category. As a corrective to these problems, we compare variation in global interest group mobilization across countries to the size of these countries' national economies. Relying on an original dataset mapping interest groups communities at the World Trade Organization (1997–2012) and the United Nations Climate Summits (1997–2011), we show that (i) global interest representation almost perfectly reflects differences in countries' relative economic power and (ii) contrary to the conventional wisdom, wealthier countries are, relative to their economic size, actually underrepresented in global interest communities.